Hubungan Kepatuhan Mengkonsumsi Tablet Fe Terhadap Kadar HB Pada Ibu Hamil Trimester III di PMB Dewiady Medical Kecamatan Margorejo Kabupaten Pati Tahun 2023 - Sri Wahyuni; Triana Widiastuti (Lembaga Pengembangan Kinerja Dosen, 2023)
Background : Pregnancy is a physiological process that through by women. Its process begins with conception to the birth process. Prevention of emergency conditions during pregnancy is detected by early detection through pregnancy checks four times by observe the development and growth of the fetus and monitor the mother’s health. During pregnancy, the mother will experience hemodilution or blood dilution so that she is at risk from anemia. Method : This research was an analytic survey with a cross sectional approach. There were 30 pregnant women in third trimester at PMB Dewiady Medical, Margorejo District, Pati Regency were selected using a purposive sampling technique. The research data consists of primary and secondary data. Data analysis between variables used the Chi Square formula. Results : As many as 20 pregnant women (66.7%) adhered to taking Fe tablets, the rest did not comply as many as 10 pregnant women (33.3%). Pregnant women without anemia reached 20 pregnant women (66.7%), while 10 pregnant women (33.3%) had mild anemia. The results of the Chi Square test obtained a value of p(<0.001) <0.05 with a calculated X2 value = 30.000 which indicates a relationship between compliance of pregnant women in consuming Fe tablets and Hb levels in pregnant women. The more obedient pregnant women are in consuming Fe tablets, the more normal the Hb levels of these pregnant women will be. Conclusion : There is a relationship between adherence in consuming Fe tablets to Hb levels of third trimester pregnant women at PMB DewiAdy Medical, Pati District, Pati Regency.